Evaluation of sexual, physical, and emotional abuse in women diagnosed with temporomandibular disorders: A case-control study - Grossi, Patrícia Krieger; Bueno, Caroline Hoffmann; Silva, Mariana Álvares de Abreu; Pellizzer, Eduardo Piza [UNESP]; Grossi, Márcio Lima (Quintessence Publishing, 2018)
Purpose: To compare the prevalence of physical and sexual abuse in women with temporomandibular disorders (TMD) vs women without TMD. Methods: Forty women (age range 16-45 years) with idiopathic TMD were selected from the Occlusion Clinic at the Pontifical Catholic University of Rio Grande do Sul Faculty of Dentistry and were compared to 40 TMD-free women within the same age range. The Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD) Axes I and II and the Sexual Abuse History Questionnaire (S/PAHQ) were used to collect data. Results: Women with TMD diagnosed with myofascial pain had higher levels of chronic pain grade, disability points, chronic pain intensity, depression, and nonspecific physical symptoms with and without pain (ie, somatization). Women with TMD were significantly less educated, had lower family income, and were older than women without TMD. They also had significantly older partners, but there were no differences in the partners' occupation or education levels. Regarding emotional abuse, women with TMD reported significantly more insults and diminishing/humiliation in front of other people than the controls. The prevalence of physical and sexual abuse was higher in the TMD group, but this difference was nonsignificant. Conclusion: Emotional abuse, more than physical and sexual abuse, is an important risk factor for the development of TMD, even when controlling for education level, income, age, ethnicity, marital status, and occupation. Emotional abuse, as well as physical and sexual violence, should be assessed routinely in women suffering from chronic TMD.